2006
DOI: 10.1038/ni1378
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors TFE3 and TFEB are critical for CD40 ligand expression and thymus-dependent humoral immunity

Abstract: TFE3 and TFEB are broadly expressed transcription factors related to the transcription factor Mitf. Although they have been linked to cytokine signaling pathways in nonlymphoid cells, their function in T cells is unknown. TFE3-deficient mice are phenotypically normal, whereas TFEB deficiency causes early embryonic death. We now show that combined inactivation of TFE3 and TFEB in T cells resulted in a hyper-immunoglobulin M syndrome due to impaired expression of CD40 ligand by CD4 + T cells. Native TFE3 and TFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 55 publications
1
64
0
Order By: Relevance
“…We and others have previously described and characterized the CD154 transcriptional promoter. 2,4,13,[18][19][20][21][22][23] In addition, we have identified a 3 0 CD154 transcriptional enhancer 5 located just downstream of the 3 0 UTR mRNA stability element. 24,25 In vitro, both the hCD154 transcriptional promoter and 3 0 enhancer element are relatively weak, despite the abundant and rapid generation of CD154 mRNA following CD4 T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously described and characterized the CD154 transcriptional promoter. 2,4,13,[18][19][20][21][22][23] In addition, we have identified a 3 0 CD154 transcriptional enhancer 5 located just downstream of the 3 0 UTR mRNA stability element. 24,25 In vitro, both the hCD154 transcriptional promoter and 3 0 enhancer element are relatively weak, despite the abundant and rapid generation of CD154 mRNA following CD4 T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Roman and colleagues have also recently shown that this region is rich in binding sites for TFE3 and TFEB transcription factors. 19 This novel 5 0 CD154 transcriptional enhancer, much like the IL-4 3 0 enhancer, 10 possesses multiple binding sites for NFAT and GATA proteins. In peripheral T cells the only GATA protein present is GATA-3, 27 and sitedirected disruption of individual GATA-3 sites within the context of reporter genes have minimal to moderate (B50% reduction) inhibitory effects on transcriptional enhancement perhaps because of the redundancy of binding sites in this region (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of Toll-like receptor 4 (TLR4) on SMS1/SMS2 knockdown macrophages after LPS stimulation. Cell surface receptors were detected as described previously (23). Briefly, control siRNA-or SMS1/2 siRNA-treated macrophages were stimulated by LPS (100 ng/ml) for 2 min and then stained with 1 mg/ml TLR4/MD-2 complex antibody (CSA-805FIJ, Stressgen) for 1 h on ice, then washed with ice-cold PBS three times before analysis on a FACScan with CellQuest software.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface receptors were detected as described previously (23). Briefly, macrophages were stimulated by LPS (100 ng/ml) for 2 min and then stained with 1 mg/ml Toll-like receptor 4 (TLR4)/MD-2 complex antibody (CSA-805FIJ; Stressgen) for 1 h on ice, then washed with ice-cold PBS three times before analysis on a FACScan with CellQuest software (Benton Dickinson).…”
Section: Toll-like Receptor 4 Analyses By Fluorescence-activated Cellmentioning
confidence: 99%
“…In addition, combined depletion of TFEB and TFE3 in T cells leads to a defective T-celldependent antibody response (Huan et al, 2006), whereas TFEB controls antigen presentation by major histocompatibility complexes (MHCs) in dendritic cells (Samie and Cresswell, 2015), suggesting a broad role for TFEB in controlling the immune response.…”
Section: Functional In Vivo Studies Of Tfebmentioning
confidence: 99%